Attitudes of Parents Living in Rural and Urban Areas in Kütahya Province Towards Childhood Vaccines - Nalan Bostan Akmeşe; Buşra Arık (Galenos Publishing House, 2023)
Objective:The aim of the study was to investigate the attitudes of parents living in rural and urban areas towards childhood vaccinations using the health belief model.Method:The study is of descriptive comparative research type. The study was carried out interviews with parents between June and September 2021. A total of 254 parents, 153 from the urban area and 101 from the rural area, participated. In the study, descriptive questionnaire, vaccine-related community attitude-health belief model scale were used as data collection tools. Descriptive statistics, Spearman correlation analysis, Kruskal-Wallis test, Mann-Whitney U test were used in the analysis of the data.Results:The total score of vaccine-related community attitude-health belief model scale was found to be 87.63±9.84 for parents in urban areas and 89±6.44 for parents in rural areas. Perceived sensitivity, perceived importance/seriousness, perceived benefit, health responsibility sub-dimensions were higher, and perceived disability sub-dimension scores were found to be lower in those who thought that childhood vaccinations were necessary and had them done (p<0.05). It was determined that 97% of parents living in rural areas and 92.2% of parents living in urban areas had the vaccines included in the childhood vaccination calendar. 67.3% of parents living in rural areas stated that "vaccination is a legal obligation and every newborn baby/child should be vaccinated compulsory".Conclusion:It has been observed that the mean scores of parents' vaccination attitude in both urban and rural areas are at a moderate level.